Chiari malformation and central sleep apnea syndrome: efficacy of treatment with adaptive servo-ventilation - Jorge Marques do Vale; Eloísa Silva; Isabel Gil Pereira; Catarina Marques; Amparo Sanchez-Serrano; António Simões Torres (Jornal Brasileiro de Pneumologia, 2014)
The Chiari malformation type I (CM-I) has been associated with sleep-disordered breathing, especially central sleep apnea syndrome. We report the case of a 44-year-old female with CM-I who was referred to our sleep laboratory for suspected sleep apnea. The patient had undergone decompressive surgery 3 years prior. An arterial blood gas analysis showed hypercapnia. Polysomnography showed a respiratory disturbance index of 108 events/h, and all were central apnea events. Treatment with adaptive servo-ventilation was initiated, and central apnea was resolved. This report demonstrates the efficacy of servo-ventilation in the treatment of central sleep apnea syndrome associated with alveolar hypoventilation in a CM-I patient with a history of decompressive surgery.